PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN MENULIS PUISI KELAS VIII SMP MUHAMMADIYAH 47 SUNGGAL TAHUN PEMBELAJARAN 2023/2024 - Rani Anggraini (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine the effect of the Think Pair Share (TPS) Cooperative learning model on the Poetry Writing Ability of Class VIII Students of SMP Muhammadiyah 47 Sunggal in the 2023/2024 Learning Year. The research is a type of quantitative research using experimental methods using a form of experimental design, namely Pre-experimental using the One Group Pretest-Posttest Design type, in this design, observations are carried out twice, namely before the experiment (O1) and the experiment (O2). The population in this study was the entire class VIII of SMP Muhammadiyah 47 Sunggal. And the sample used in this research was class VIII-1 SMP Muhammadiyah 47 Sunggal with 27 students. In this study, researchers used purposive sampling techniques. The instrument for this research is a test. From the results of research on the ability to write poetry, the results obtained were that the ability to write poetry before using the think pair share type cooperative learning model in class VIII students of SMP Muhammadiyah 47 Sunggal in the 2023/2024 academic year obtained an average score of 63.3333. The ability to write poetry after using the think pair share type cooperative learning model for class VIII students of SMP Muhammadiyah 47 Sunggal in the 2023/2024 academic year obtained an average score of 81.8889. Based on analysis of research data, the t test with a significance level of 0.05, with dk = N – 1 = 27 – 1 = 26, and obtained a 5% significance level of 1.3. Based on the t-table value mentioned above, it can be concluded that t-count > t-table, namely 12.7969 > 1.3 so that Ho is rejected and Ha is accepted. This proves that there is a significant influence on the use of the cooperative learning model. think pair share (TPS) in improving writing skills in class VIII students of SMP Muhammadiyah 47 Sunggal in the 2023/2024 learning year.